Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s13099-016-0147-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics analyses revealed two virulent Listeria monocytogenes strains isolated from ready-to-eat food

Abstract: Background Listeria monocytogenes is an important foodborne pathogen that causes considerable morbidity in humans with high mortality rates. In this study, we have sequenced the genomes and performed comparative genomics analyses on two strains, LM115 and LM41, isolated from ready-to-eat food in Malaysia.ResultsThe genome size of LM115 and LM41 was 2,959,041 and 2,963,111 bp, respectively. These two strains shared approximately 90% homologous genes. Comparative genomics and phylogenomic analyses revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The antibiotic resistance genes tetM and ermB were also identified in L. monocytogenes isolated from fresh mixed sausage and chicken slaughterhouse, respectively (Haubert et al., ). Recently, Lim, Yap, and Thong () found that two L. monocytogenes isolates from fried fish and salad carried five genes including tetA , lmrB , mecC , msrA , and fosX that confer resistance to tetracycline, lincomycin, beta‐lactam, erythromycin, and fosfomycin, respectively. Wilson et al.…”
Section: Mechanisms Of Antibiotic Resistance In L Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiotic resistance genes tetM and ermB were also identified in L. monocytogenes isolated from fresh mixed sausage and chicken slaughterhouse, respectively (Haubert et al., ). Recently, Lim, Yap, and Thong () found that two L. monocytogenes isolates from fried fish and salad carried five genes including tetA , lmrB , mecC , msrA , and fosX that confer resistance to tetracycline, lincomycin, beta‐lactam, erythromycin, and fosfomycin, respectively. Wilson et al.…”
Section: Mechanisms Of Antibiotic Resistance In L Monocytogenesmentioning
confidence: 99%
“…Lim et al. () detected two efflux pump‐related genes, mdrL and lde , which confer resistance to macrolides and quinolone, respectively, in the genomes of two L. monocytogenes isolates from fried fish and salad. In another study, it was suggested that the mutation in the fluoroquinolone efflux protein ( fepA ) regulator, fepR , is responsible in part for the resistance of L. monocytogenes to ciprofloxacin (Wilson et al., ).…”
Section: Mechanisms Of Antibiotic Resistance In L Monocytogenesmentioning
confidence: 99%
“…Overall, the cooperative binding and unique mode of metal recognition by the NiCo riboswitch impart high selectivity, enabling feedback to minute changes in Co 2ϩ or Ni 2ϩ in a milieu of competing cellular ions to confer heavy-metal resistance. Notably, NiCo riboswitches are present in Listeria monocytogenes, a common foodborne pathogen (60) that is of concern because of the identification of multi-antibiotic resistance isolates in "ready-to-eat"' foods (61).…”
Section: Nico Riboswitches Confer Heavy Metal Resistance By Sensing Nmentioning
confidence: 99%
“…Fluoroquinolone resistance may be mediated by mutations in quinolone resistance-determining regions, including GyrA, GyrB, ParC, and ParE (Bertrand et al, 2016). In addition, the expression of efflux pump FepR, MdeL, and Lde contributed to resistance toward fluoroquinolones (Lismond et al, 2008;Guerin et al, 2014;Lim et al, 2016;Wilson et al, 2018). Vancomycin and novel β-lactams constitute last-line therapy for Listeria infections, and no resistant isolate was observed herein.…”
Section: Discussionmentioning
confidence: 79%